(untitled) (Journal of EAHIL, 2015)
The story began during Ludovic Hery’s residency. He was asked by his friends to help them with using PubMed. HeÂ had the idea to produce short tutorials on video; he realised that for students it was an appropriate way of learning,Â especially for information retrieval. L. Hery shot 28 tutorials about PubMed and Zotero in the first place, with the help of other residents and healthÂ librarians. The project is now carried out by health librarians from French University libraries. Called DocToBib, itÂ relies on a YouTube channel, whose success is real, thanks to social networks. DocToBib is an example of a successfulÂ collaboration involving physicians and health librarians.